The potential of impact narratives for social entrepreneurship - Pascal Nissing (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2023)
Social Entrepreneurship is a growing field of practice and research. But solving social ills with innovative solutions and business approaches entails the need to assess the social businesses' success, their impact. While impact measurement is a dominant topic in research, the paper at hand aims to analyze the step taken prior to measurement. With impact understanding, the focus lies on the way social enterprises understand and capture the full scope of their impact. The Impact Narrative tool is a newly developed tool that aims at helping multi-stakeholder partnerships to develop and capture their impact understanding. This research examines the potential of this tool for social enterprises to enhance their impact understanding. By conducting five qualitative interviews with experts on social enterprises and their impact, different aspects of impact understanding could be analyzed. Insights on used methodologies, the communication of impact, and reasons and challenges in understanding one's impact enabled an assessment of the potential of the Impact Narrative tool for social entrepreneurship. The qualitative content-structuring analysis after Kuckartz allowed coding the resulted data to find answers to the relevant topics and connections within. Although reactions to the tool are different, the challenges facing social entrepreneurs when developing an impact understanding and their reasons to do so are similar. The importance of impact communication, the challenging need to acquire resources, and the strategic clarity that social enterprises hope for, are just a few of the insights gained. With detailed impact levels and dimensions, a diversified version of the Impact Value Chain, and a specific visual style, the Impact Narrative tool does not solve issues of quantification. However, the tool enables a systematically developed and enhanced understanding of one's scope of impact that can help a social enterprise to develop and improve, internally and externally.
Keywords: 650; Entrepreneurship; Impact; qualitative; expert interviews; Sozialwirtschaft; Soziale Folgen; Narrative Methode; Befragung